RESPONSABILIDAD ADMINISTRATIVA EN EL DEPARTAMENTO DE TESORERÍA DEL GOBIERNO AUTÓNOMO DESCENTRALIZADO PARROQUIAL RURAL SAN JUAN - Gomez Espin, Mercedes Antonela (2019)
The Autonomous Decentralized Parochial Rural Government San Juan, is a public institution that is located in the Parish of San Juan de Juana de Oro in the streets May 24 and León de Febres Cordero, in a building of the institution in which they have come developing its activities since 2014 to the present. The objective of this case study is to determine the administrative responsibilities in the treasury department of the San Juan Rural Parochial Decentralized Autonomous Government, which will allow establishing the causes that affect the correct performance of the institution's activities, which are planned and programmed by its authorities in conjunction with its administrative staff. The research sub-line on which the present case study is based is Administrative Management Model that refers to the administration in the treasury department of the San Juan Rural Parochial Decentralized Autonomous Government during the years 2016 and 2017 by the treasurer, which reflected the various problems that the institution had to go through in the years analyzed